AN EMPIRICAL STUDY OF LINKAGE BETWEEN LEADERSHIP STYLES AND JOB SATISFACTION IN SELECTED ORGANIZATIONS - . Vipin Jain, Enaidy Reynosa Navarro, Dr. Worakamol Wisetsri, Dr. Sevdie Alshiqi (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The purpose of this study is to explore the effects on job satisfaction and to explore the possible impact of types of transformative and transactional leadership. A quantitative analysis was carried out, which analyzed the relationship that is being talked about. A total of 242 employees and managers from a selection of organizations were selected for the experiment. A self-report measure is used for the Multifactor Leadership Questionnaire and the Minnesota Satisfaction Questionnaire to measure leadership and job satisfaction. It was shown that the variables that were tested in the study were not only meaningful and positive, while the results reflected that the variables were effectively handled. Multiple regression studies have shown that those who are in positions of leadership are highly satisfied in their jobs because of their ability to lead, as well as the way they- their style and thoughtfulness- affects the satisfaction in a group. It is ironic that the participating managers were very satisfied with the results of the transformative programme